Agama dan Ekonomi Kaum Tertindas - Muh. Yunus (UIN Maulana Malik Ibrahim Malang, 2006)
As what Weber and Mc. Lelland view, it is assumed that values in certain religion and culture are believed to be able to influence the followers' behavior which are implied on the economic growth. Although indirectly they influence the economic development. Although Islam teaches about the work culture, the relity shows that Indonesian econmy has been well-develop yet. Religion (Islam) as Weber critisizes, does not result in capitalism industrialization as the motivator of economic development because the culture is in line with The Spirit of Capitalism. It is different from Calvinism; its theology is able to move the economy development of its followers. Therefore, the Moslems' problem of economic decrease has to be solved with a right strategy. In this paper, the strategy used to solve the problem is macro analysis through the model of M. Chapra' s cycle theory. Seperti apa Weber dan Mc. Pandangan lelland, diasumsikan bahwa nilai-nilai dalam agama dan budaya tertentu diyakini dapat mempengaruhi perilaku pengikut yang tersirat pada pertumbuhan ekonomi. Meski secara tidak langsung mereka mempengaruhi perkembangan ekonomi. Meskipun Islam mengajarkan tentang budaya kerja, relitas menunjukkan bahwa ekonmy Indonesia telah berkembang dengan baik. Agama (Islam) seperti yang dikemukakan Weber, tidak mengakibatkan industrialisasi kapitalisme sebagai motivator pembangunan ekonomi karena budayanya sejalan dengan The Spirit of Capitalism. Hal ini berbeda dengan Calvinisme; Teologinya mampu menggerakkan perkembangan ekonomi para pengikutnya. Oleh karena itu, masalah penurunan ekonomi umat Islam harus dipecahkan dengan strategi yang tepat. Dalam tulisan ini, strategi yang digunakan untuk memecahkan masalah adalah analisis makro melalui model teori siklus M. Chapra.